Exploration of neuroprotective effect from Coriandrum sativum L. ethanolic seeds extracts on brain of obese rats - Hardiany, Novi Silvia; Dewi, Putri Krishna Kumara; Dewi, Syarifah; Tejo, Bimo A. (Nature Research, 2024)
In this study, the potential neuroprotective ability of coriander seeds (Coriandrum sativum L.) ethanolic extract (CSES) as a neuroprotectant agent in the brains of high-fat diet-induced obese rats was analyzed. The study investigated how CSES impacts oxidative stress markers (i.e., malondialdehyde/MDA, glutathione/GSH and catalase), inflammation marker (i.e., Interleukin-6/IL-6), cellular senescence markers (i.e., senescence-associated β-galactoside/SA-β-Gal activity and p16), brain damage marker (i.e., Neuron-specific Enolase/NSE), and neurogenesis markers (i.e., mature Brain-derived Neurotropic Factor/BDNF, pro-BDNF, and mature/pro-BDNF ratio). Male adult Wistar rats were fed a high-fat diet and given CSES once daily, at 100 mg/kg body weight, for 12 weeks. CSES significantly reduced MDA concentration (p = < 0.001), SA-β-Gal activity (p = 0.010), and increased GSH concentration (p = 0.047) in the brain of obese rats; however, the decrease of IL-6, NSE, and p16 as well as the increase of catalase specific activity and BDNF expression were not significant. Moreover, the mature/pro-BDNF ratio was significantly higher in the brains of non-obese rats, both given the control diet and the high-fat diet compared to the control. Our results suggest that obese rats benefited from consuming CSES, showing improved oxidative stress levels, reduced cellular senescence and increased endogenous antioxidants, making CSES a potential neuroprotective agent.